SYNTHESIS AND IN-VITRO STUDY OF SOME MEDICINALLY IMPORTANT MANNICH BASES DERIVED FROM 2-AMINO-9 [{(1, 3 DIHYDROXY PROPANE-2YL) OXY} METHYL] 6-9 DIHYDRO-3H-PURIN-6-ONE - JOSHI,SHEELA (Sociedad Chilena de Química, 2012)
A series of biologically active Mannich bases with heteroaromatic ring system have been synthesized employing Mannich reaction of 2-amino-9 [{(1,3 dihydroxy propane-2yl) oxy}methyl] 6-9 dihydro-3H-purin-6-one ( potent drug) with biologically active sulphonamides and secondary amines. They were analyzed by elemental analysis and characterized by spectral studies- UV, IR, ¹H NMR, Powder X-ray diffraction and Scanning Electron Microscopy. The Mannich bases were screened for their antibacterial activity against various gram + and gram - bacteria. The results had shown that the Mannich bases are quiet active against pathogens under study at varying concentrations. The toxicity of synthesized Mannich bases was ascertained by LD50 test.